Synthesis of metal nanoparticles on graphene oxide and antibacterial properties - Tene, Talia; Bellucci, Stefano; Pachacama, Joseth; Cuenca-Lozano, María F.; Tubon-Usca, Gabriela; Guevara, Marco; La Pietra, Matteo; Cruz Salazar, Yolenny; Scarcello, Andrea; Arias Polanco, Melvin; Gahramanli, Lala Rasim; Vacacela Gomez, Cristian; et al. (Frontiers in Chemistry, 2024)
Pathogen-induced infections and the rise of antibiotic-resistant bacteria, such as Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus), pose significant global health challenges, emphasizing the need for new antimicrobial strategies. In this study, we synthesized graphene oxide (GO)-based composites functionalized with silver nanoparticles (AgNPs) and copper nanoparticles (CuNPs) as potential alternatives to traditional antibiotics. The objective is to assess the antibacterial properties of these composites and explore their efficacy against E. coli and S. aureus, two common bacterial pathogens. The composites are prepared using eco-friendly and conventional methods to ensure effective nanoparticle attachment to the GO surface. Structural and morphological characteristics are confirmed through SEM, AFM, EDS, XRD, UV-vis, FTIR, and Raman spectroscopy. The antibacterial efficacy of the composites is tested through disk diffusion assays, colony-forming unit (CFU) counts, and turbidimetry analysis, with an emphasis on understanding the effects of different nanoparticle concentrations. The results demonstrated a dose-dependent antibacterial effect, with GO/AgNP-1 showing superior antibacterial activity over GO/AgNP-2, particularly at lower concentrations (32.0 μg/mL and 62.5 μg/mL). The GO/CuNP composite also exhibited significant antibacterial properties, with optimal performance at 62.5 μg/mL for both bacterial strains. Turbidimetry analysis confirmed the inhibition of bacterial growth, especially at moderate concentrations, although slight nanoparticle aggregation at higher doses reduced efficacy. Lastly, both GO/AgNP and GO/CuNP composites demonstrated significant antibacterial potential. The results emphasize the need to fine-tune nanoparticle concentration and refine synthesis techniques to improve their efficacy, positioning these composites as strong contenders for antimicrobial use.